2019
DOI: 10.1037/aca0000169
|View full text |Cite
|
Sign up to set email alerts
|

The creative self and creative thinking: An exploration of predictive effects using Bayes factor analyses.

Abstract: The present research explored the relationship between the creative self and creative performance. Based on prior research purporting that perceptions of the self can predict behavior, the authors predicted that beliefs about the creative self would predict creative performance. Participants completed two scales on beliefs about their creativity (creative self-efficacy; fixed and growth mindsets about creativity), and then completed two types of creativity tasks: three divergent thinking tasks and one creative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 67 publications
(131 reference statements)
3
25
0
Order By: Relevance
“…Four items measuring fixed mindset items were adapted from Karwowski’s (2014) creative mindset scale. Karwowski’s original scale had five fixed mindset items, but one was dropped that consistently exhibited low factor loadings in other studies using the scale (e.g., Hass et al, 2018; Katz‐Buonincontro et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four items measuring fixed mindset items were adapted from Karwowski’s (2014) creative mindset scale. Karwowski’s original scale had five fixed mindset items, but one was dropped that consistently exhibited low factor loadings in other studies using the scale (e.g., Hass et al, 2018; Katz‐Buonincontro et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Four growth creative mindset items were also adapted from Karwowski’s (2014) creative mindset scale. This subscale tends to show fair internal consistency (Hass et al, 2018) and tends to show a negative correlation with fixed mindset, though they are generally viewed as separate constructs (Karwoski et al, 2019). We used a 4‐item version, rather than Karwowski’s 5‐item version, as prior research showed lower factor loadings for one of the items (Katz‐Buonincontro et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations